An Analysis of Students’ Errors in Solving Mathematical Problems on Trigonometric Materials - Febrini Rizki Pilianna; Diyah Hoiriyah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
This article aims to describe the mistakes made by students in solving mathematical problems in trigonometric materials. This research is a descriptive study with the object of research is class X-MIA MAN 1 Padangsidimpuan with heterogeneous levels of ability. The instrument collects data using essay tests. Data analysis is carried out by reducing the data in the form of paragraphs and images, then drawing conclusions. The results of this study show that the common mistakes made by students in this study are more errors in understanding the problem, errors in planning problem solving, errors in doing calculations and errors in re-examining the answers, namely wrong in understanding the meaning of the question information, not fully understanding the formulas that must be used in doing the questions, errors in the calculation process and students did not find the results requested in the questions,  and the error did not re-check the answer and did not carry out the stages of re-checking.